Seabird guild composition and distribution relative to biophysical cues throughout the Antarctic Peninsula and Scotia Sea - Ollus, Victoria Marja Sofia (UiT Norges arktiske universitet, 2021)
Seabird distributions reflect physical and biological features of the marine environment and their variability on different spatial and temporal scales. Different species assemblages are associated with specific oceanic habitats and concentrations of birds typically occur in areas of high biological productivity. Here I explore seabird distributions and habitat use relative to biophysical cues of biological productivity throughout the Antarctic Peninsula and Scotia Sea in austral summer. Data on seabird at-sea distributions were collected through strip-transect counts using tourism vessels as opportunistic sampling platforms. Multivariate statistical methods and generalized additive models (GAM) were used to relate seabird guild composition, abundance, and species richness to environmental covariates. Sea surface temperature (SST) and distance to coast were the most important predictors of seabird distributions. Species assemblages differed between oceanographic zones and increased abundance and species richness were encountered in generally productive areas, such as coastal regions and oceanographic fronts. Coastal areas, particularly South Georgia, were important for seabirds at the time of our survey, which coincided with the breeding season for several bird species in the area. These findings highlight the importance of environmental features on seabird distributions and habitat use. Fine-resolution community-level data on marine top predator distributions are needed when assessing change, predicting habitat shifts, and ultimately to base successful conservation measures and management decisions on. This study shows that seabird distribution data collected cost-effectively using tourism vessels as platforms of opportunity can be a valuable addition to structured surveys.